LEVEL OF MOTIVATION AND SATISFACTION IN PRACTITIONERS SPINNING® (Fiep Bulletin - online, 2011)
This study aimed to detect individually as is the motivation and satisfaction in beginning students and experienced and what keeps them motivated and happy to continue the practice of Spinning ®. This is a field which were administered to students of the Academy ® Spinning Top Fitness Maceió-AL where the researcher minister their classes. We plotted the questionnaires to 60 students who were willing to cooperate with our research. We can conclude that this relationship between body and mind, "is nothing more than the cornerstone of any physical activity that you can run and have a good recovery, knowing that when you have no concentration field of the main reactions that come into your body can thus work them and improve them evenly in terms of goals to meet. Soon it becomes clear how important this is theoretical material available for those interested in the sport and are attracted by the practice of Spinning ®, with all the security of choice, the benefits that aims to achieve the satisfaction gained by a reason to be guided by certain motivated by internal forces or impulses that saceiam a desire for a better quality of life and is the main reason to determine the motivation and personal satisfaction of each student in the sense of well-being and pleasure.
Keywords: Motivation; Satisfaction and Spinning